1981
DOI: 10.1136/hrt.46.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Borderline low thyroid function and thyroid autoimmunity. Risk factors for coronary heart disease?

Abstract: Assessments were made of 945 consecutive hospital patients with regard to a relation between borderline low thyroid function (recognised by a slightly raised thyroid stimulating hormone), thyroid autoimmunity, serum cholesterol, and coronary heart disease. Men and women with a thyroid autoimmunity, serum cholesterol, and coronary heart disease. Men and women with a thyroid stimulating hormone of 4.0 mU/l or over had a higher prevalence of coronary heart disease than did age-matched controls, and this differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 18 publications
3
40
4
Order By: Relevance
“…First, coronary vascular stenosis is induced by local inflammation from the pathological immune reactivity in thyroid autoimmunity that may be found in most patients with SHT. 16,17 However, this suggestion was not confirmed by other studies. 13,15 Second, previous studies have clearly shown that patients with SHT have left ventricular diastolic dysfunction at rest that is reversible with thyroxine therapy 18,19 and systolic dysfunction on effort, which may result in poor physical exercise capacity.…”
Section: Discussioncontrasting
confidence: 52%
“…First, coronary vascular stenosis is induced by local inflammation from the pathological immune reactivity in thyroid autoimmunity that may be found in most patients with SHT. 16,17 However, this suggestion was not confirmed by other studies. 13,15 Second, previous studies have clearly shown that patients with SHT have left ventricular diastolic dysfunction at rest that is reversible with thyroxine therapy 18,19 and systolic dysfunction on effort, which may result in poor physical exercise capacity.…”
Section: Discussioncontrasting
confidence: 52%
“…Notably, in that study, FL was significantly more prevalent in SCH patients than in euthyroid subjects, suggesting a possible role of the increased hepatic fat in the associations (7). With regard to cardiovascular disease, some (10,33), but not all (14,34), published studies have reported associations between SCH and CHD. An interesting recent study by Sert et al (35) has demonstrated that obese adolescents with FL and SHC had a proatherogenic metabolic risk factor profile and a higher carotid intimamedia thickness and left ventricular mass.…”
Section: European Journal Of Endocrinologymentioning
confidence: 82%
“…Taken together, our results and those of other studies (36,37,38,39) strongly suggested that hepatic fat is intimately involved in the pathogenesis of metabolic abnormalities and subclinical atherosclerosis present in subjects with FL. The adverse cardiovascular risk profile found in subjects with SCH plus FL may serve as a marker of long-term cardiovascular risk and may explain some of the previously observed associations between SCH and cardiovascular disease (10,33). …”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…Data from small case-control and cross-sectional studies have indicated a link between subclinical hypothyroidism and coronary artery disease (Tieche et al 1981, Dean & Fowler 1985. A large Dutch study has reported the association between subclinical hypothyroidism and aortic calcification as well as myocardial infarction amongst a cohort of 1149 women living in Rotterdam (Hak et al 2000).…”
Section: Thyroid Hormone and The Heartmentioning
confidence: 99%